E.M Forster‟s A Passage to India as a Postcolonial Novel - Dudeja , Mahek; Vashist, Shivani (International Journal of Psychosocial Rehabilitation, 2020)
The term ‘Post Colonialism’ refers to the representation of race, ethnicity, culture, and human identity in the modern era, mostly after many colonized countries got their independence from European powers. Dating back to the time of the 16th century, the colonial and imperial encounter between the west and the non-west has led to historical, political, and cultural ramifications often dictating a Eurocentric superiority on the natives, who are perceived to be inferior, barbaric, and uncivilized. In an attempt to dominate inferior people, the colonial ruler has often set out to suppress their culture and tradition, as well as tried to suppress them with their own language. These acts of suppression were resisted by natives in order to save their indigenous languages, cultures, and lifestyles. In literature, writers present the era of postcolonialism with common motifs and themes like ‘identity’, ’language’, and ‘racism’. Some remarkable works are Things Fall Apart, Midnight’s Children, Disgrace, The English Patient, and many more. In my research paper, I will explore the work The Passage to India written by E.M. Forster. The novel is a realistic document about the British rule in India. This paper aims to analyze A Passage to India as a postcolonial, anti-imperialistic text and will also emphasize the psychological barriers and prejudices projected in the novel.